EFL Students' Perception of Utilizing the Wattpad Application as Learning Media in Reading - Samosir, Sri Aulia; Daulay, Sholihatul Hamidah; Dewi, Utami (LPPM STKIP Kusuma Negara, 2024)
This study aims to determine how students' perspectives of utilizing the wattpad application as learning media in reading. Ten EFL students from Indonesia majoring in English education participated in this study. This study gathered both quantitative and qualitative data through the use of semi-structured interviews, as well as open-ended and closed-ended questionnaires. The open-ended questionnaire delved into the advantages and disadvantages of using the Wattpad application, while the closed-ended questions gauged the frequency of students' use of the Wattpad application. Simultaneously, the semi-structured interview questions were crafted based on participants' responses to the questionnaires. Most participants found the Wattpad app valuable and user-friendly. They consider the Wattpad app as a valuable tool for language learning, inspiring independent study. The findings indicate that novice learners can derive greater benefits from mobile apps compared to experts. The research results show that students had positive views on using Wattpad as a reading application to enhance their skills. The study also outlines both the advantages and drawbacks of utilizing the Wattpad program. Students identified key benefits of extensive reading on Wattpad, such as user-friendliness, convenience, flexibility, and cost savings. These factors not only motivate increased reading but also inadvertently enhance students' writing abilities.